2017
DOI: 10.1088/1478-3975/aa7bb3
|View full text |Cite
|
Sign up to set email alerts
|

Convection shapes the trade-off between antibiotic efficacy and the selection for resistance in spatial gradients

Abstract: Since penicillin was discovered about 90 years ago, we have become used to using drugs to eradicate unwanted pathogenic cells. However, using drugs to kill bacteria, viruses or cancer cells has the serious side effect of selecting for mutant types that survive the drug attack. A key question therefore is how one could eradicate as many cells as possible for a given acceptable risk of drug resistance evolution. We address this general question in a model of drug resistance evolution in spatial drug gradients, w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 66 publications
(128 reference statements)
0
21
0
Order By: Relevance
“…However, the effects of such environmental heterogeneity, which can be viewed as a source of extrinsic noise, on evolutionary dynamics in microbial populations have received much less attention. Efforts have concentrated mostly on simple temporal and spatial gradients in antibiotic concentration, which have been shown to facilitate the emergence of resistance in shaken cultures [37], microfluidic devices [51] and on agar plates [4], as predicted by theory [20,23,[25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…However, the effects of such environmental heterogeneity, which can be viewed as a source of extrinsic noise, on evolutionary dynamics in microbial populations have received much less attention. Efforts have concentrated mostly on simple temporal and spatial gradients in antibiotic concentration, which have been shown to facilitate the emergence of resistance in shaken cultures [37], microfluidic devices [51] and on agar plates [4], as predicted by theory [20,23,[25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, evolutionary biologists have long recognized resistance as a fundamentally stochastic process governed by the complex interplay between microbial ecology and evolutionary selection. The last decade, in particular, has seen a significant surge in efforts to develop and understand evolution-based treatment strategies to forestall resistance [516]. While the vast majority of this work focuses on spatially homogeneous environments, a number of recent studies, both theoretical and experimental, have demonstrated that spatial heterogeneity in drug concentration can dramatically alter the evolutionary dynamics leading to resistance [1624].…”
mentioning
confidence: 99%
“…The last decade, in particular, has seen a significant surge in efforts to develop and understand evolution-based treatment strategies to forestall resistance [516]. While the vast majority of this work focuses on spatially homogeneous environments, a number of recent studies, both theoretical and experimental, have demonstrated that spatial heterogeneity in drug concentration can dramatically alter the evolutionary dynamics leading to resistance [1624]. On a practical level, the picture that emerges is somewhat bleak, as resistance evolution is dramatically accelerated in the presence of spatial gradients in drug concentration [1820, 2224] or heterogeneous drug penetration [17, 21].…”
mentioning
confidence: 99%
“…At the same time, evolutionary biologists have long recognized resistance as a fundamentally stochastic process governed by the complex interplay between microbial ecology and evolutionary selection. The last decade, in particular, has seen a significant surge in efforts to develop and understand evolution-based treatment strategies to forestall resistance [5][6][7][8][9][10][11][12][13][14][15][16]. While the vast majority of this work focuses on spatially homogeneous environments, a number of recent studies, both theoretical and experimental, have demonstrated that spatial heterogeneity in drug concentration can dramatically alter the evolutionary dynamics leading to resistance [16][17][18][19][20][21][22][23][24].…”
mentioning
confidence: 99%
“…The last decade, in particular, has seen a significant surge in efforts to develop and understand evolution-based treatment strategies to forestall resistance [5][6][7][8][9][10][11][12][13][14][15][16]. While the vast majority of this work focuses on spatially homogeneous environments, a number of recent studies, both theoretical and experimental, have demonstrated that spatial heterogeneity in drug concentration can dramatically alter the evolutionary dynamics leading to resistance [16][17][18][19][20][21][22][23][24]. On a practical level, the picture that emerges is somewhat bleak, as resistance evolution is dramatically accelerated in the presence of spatial gradients in drug concentration [18][19][20][22][23][24] or heterogeneous drug penetration [17,21].…”
mentioning
confidence: 99%